2006
DOI: 10.1002/ajpa.20454
|View full text |Cite
|
Sign up to set email alerts
|

Secondary osteon and Haversian canal dimensions as behavioral indicators

Abstract: Variation in the size of structures within mature cortical bone is relevant to our understanding of apparent differences between human samples, and it is relevant to the development of histologically based age-estimation methods. It was proposed that variation may reflect effects of physical activity, through biomechanical and/or metabolic mechanisms. If these factors are local, femoral osteon area (On.Ar) should be more histologically variable than On.Ar in ribs. Ribs should show a higher variation in Haversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
124
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 43 publications
(40 reference statements)
2
124
0
Order By: Relevance
“…Variation has been reported at various organizational levels, from the bone to the population. A tendency for secondary osteons to be smaller in older people has been reported (Takahashi et al, 1965; Han et al, 2009), but the absence of this relationship has also been noted (Black et al, 1974; Burr et al, 1990; Pfeiffer et al, 2006; Lee et al, 2014). Recent study of cortical bone of the femoral neck region has reported a significant negative association between On.Ar and age (Tong et al, 2015), while another study reports a negative association between On.Ar and body weight, but not age (Britz et al, 2009).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Variation has been reported at various organizational levels, from the bone to the population. A tendency for secondary osteons to be smaller in older people has been reported (Takahashi et al, 1965; Han et al, 2009), but the absence of this relationship has also been noted (Black et al, 1974; Burr et al, 1990; Pfeiffer et al, 2006; Lee et al, 2014). Recent study of cortical bone of the femoral neck region has reported a significant negative association between On.Ar and age (Tong et al, 2015), while another study reports a negative association between On.Ar and body weight, but not age (Britz et al, 2009).…”
mentioning
confidence: 94%
“…On.Ar variability has been documented to vary among diverse samples (Takahashi et al, 1965; Takahashi and Frost, 1966; Pfeiffer et al, 2006), without clear causative factors being identified. Variation has been reported at various organizational levels, from the bone to the population.…”
mentioning
confidence: 99%
“…The existence of difference in patterns of bone microstructures has been an important concern in histological age estimation techniques. Bones with different size of osteons and haversian canals exhibits different osteon population densities and will reach to asymptotes at different stages of age [18]. Bone microstructures were identified to have difference with age [19], [20], [21], [22] and activity and varies with population and ancestry [18], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Bones with different size of osteons and haversian canals exhibits different osteon population densities and will reach to asymptotes at different stages of age [18]. Bone microstructures were identified to have difference with age [19], [20], [21], [22] and activity and varies with population and ancestry [18], [23], [24], [25]. Some researchers reported the difference in bone microstructures especially osteons with gender [26] while other found no such difference [24].…”
Section: Introductionmentioning
confidence: 99%
“…Chinsamy & Raath, 1992;Hillier & Bell, 2007). Bone microscopy assessment is done in wide range of research, such as ontogeny (Chimsamy, 1995;Goldman et al, 2009), comparative anatomy (Hill, 2006;Cvetkovic et al, 2013), human-osteology (Cuijpers, 2006), forensic anthropology (Pfeiffer et al, 2006;Kim et al, 2007) and diagenesis studies (Bell, 2008;Kontopoulos et al, 2016), to name just a few. Thus, the production of readable thin sections for these diverse research purposes is an essential requirement in order to facilitate these fields of research.…”
Section: Introductionmentioning
confidence: 99%